Public office and people co-administration in local development planning - ROENGTAM, S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study focus on the appropriate approach to promote the engagement of citizens in the local development planning process. It uses interviews and focus group discussions with relevant groups. It was found that local government structures have been characterized by low centralization and high levels of connectedness. Besides structure, organizational culture has been considered to reinforce citizen engagement to be institutionalized in local development planning. Local government creates processes that can support citizens and community organizations. Finally, the local development planning presented by this study highlights the role of citizen engagement and local governance.RESUMEN Este estudio trata sobre el enfoque apropiado para promover la participación de los ciudadanos en el proceso de planificación del desarrollo local. Se utilizaron entrevistas y discusiones de grupos focales con grupos relevantes. Se encontró que las estructuras del gobierno local se han caracterizado por una baja centralización y altos niveles de conexión. Además de la estructura, se ha considerado que la cultura organizacional refuerza el compromiso ciudadano. El gobierno local crea procesos que pueden apoyar a los ciudadanos y las organizaciones comunitarias. Finalmente, la planificación del desarrollo local presentada por este estudio destaca el papel del compromiso ciudadano y la gobernanza local.